Factors Associated with Goal Achievement in Patients with Dyslipidemia in Primary Care - Pinto-González, Gustavo; Uribe-Velez, Natalia Andrea; Quirós-Gómez, Oscar Iván (Iatreia)
Introduction: Dyslipidemia promotes atherosclerotic disease. A strategy to reduce this risk is to achieve low-density lipoprotein (LDL) goals; however, these are often not attained. Objectives: To analyze variables associated with achieving proposed goals in primary care. Methods: A cross-sectional study with an analytical approach was conducted. Sociodemographic variables, comorbidities, cardiovascular risk categories, and statin use were included. Binomial regression was performed to obtain crude prevalence ratios (PR), and a multivariate model was used to determine variables associated with achieving LDL goals, represented by adjusted prevalence ratios (aPR). Results: 147 patients were included. The median age was 63 years. 62.6% were female. 88.4% of patients were hypertensive. 43.5% had very high cardiovascular risk, and only 34.7% of patients met LDL goals. Factors associated with goal achievement in the bivariate analysis were: sex, diabetes, hypertension, cardiovascular risk, and statin intensity and type. In the multivariate model, being male (aPR 1.69), age (aPR 1.03), and hypertension (aPR 6.59) were significant; as was the degree of risk classified by guidelines: high risk (aPR 0.44), very high (aPR 0.07), and extreme (aPR 0.01). Conclusions: LDL goal achievement in primary care is low. The main factors associated with achieving LDL goals are age, sex, and hypertension; while high cardiovascular risk is a factor that hinders goal attainment.